2019
DOI: 10.1021/acs.jafc.9b03601
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Analysis of Epoxidized and Hydroperoxidized Triacylglycerols in Canola Oil and Margarine by LC-MS

Abstract: The progress of lipid oxidation in foods is evaluated by measuring the peroxides and their scission products. However, hydrogen abstraction-independent pathways are not considered by commonly applied methods despite the known reactivity of epoxides toward biomolecules. Herein, a novel liquid chromatography tandem-mass spectrometry method was developed to detect hydroperoxidized and epoxidized triacylglycerols (TAGs) without derivatization or hydrolyzation of food samples. Epoxidized TAGs could be detected in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 49 publications
0
30
0
Order By: Relevance
“…It is noteworthy that considering the only hexanal, as usually appears in the literature, as a secondary oxidation marker, would have led to the misleading conclusion that OPAs in the water phase were more effective towards secondary oxidation. The adopted oxidomics approach, instead, allowed to depict a more complete view of the mechanisms of action of these molecules [ 5 , 8 , 11 , 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that considering the only hexanal, as usually appears in the literature, as a secondary oxidation marker, would have led to the misleading conclusion that OPAs in the water phase were more effective towards secondary oxidation. The adopted oxidomics approach, instead, allowed to depict a more complete view of the mechanisms of action of these molecules [ 5 , 8 , 11 , 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Decker et al [ 4 ] pointed out various hurdles in predicting the effectiveness of antioxidants in real emulsions: the involvement in non-free radical scavenging reactions, the presence of different types of interfaces, inherent obstacles in studying lipid droplets properties, and varying oxidation kinetics in different droplets. Moreover, several contributions have recently suggested the expansion of traditional analytical patterns to a wider range of oxidation products to better understand oxidative phenomena [ 5 , 6 , 7 ]. Three distinct viewpoints by Paradiso, Villeneuve, and Laguerre discussed the need for a new step to study lipid oxidation in emulsified systems by focusing on different aspects [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the grape seed oil was characterized regarding the single polyphenols via high-resolution LC-MS analysis, the amount of tocopherols via HPLC/UV detection [13], the determination of fatty acids via GC/FID analysis [14] and the peroxide value using titration [15] before and after in vitro digestion.…”
Section: Methodsmentioning
confidence: 99%
“…Amber glass vials were cleaned according to Grüneis et al [14] to remove all traces of lipids and lipid-oxidation-promoting agents.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Monoepoxy and diepoxy fatty acids are detected in a wide variety of fat-or oil-containing processed foods, and their mean concentrations ranged from 13 ppm in cooked meat to 687 ppm in dry nuts (Mubiru et al, 2017;Fankhauser-Noti et al, 2006). It has been also reported that the concentrations of epoxides are higher than those of peroxides during the initial lipid oxidation in canola oil and margarine (Grüneis et al, 2019). Dietary epoxy fatty acids can be orally absorbed in healthy humans (Wilson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%